Diversity of understory birds in old stands of native and Eucalyptus plantations - Lopes, Ileyne T.; Gussoni, Carlos O.A. [UNESP]; Demarchi, Layon O.; de Almeida, Alexandre; Pizo, Marco A. [UNESP] (Wiley, 2015)
We compared the vegetation structure between old (>70 year) stands of planted diversified native forests and stands of Eucalyptus tereticornis embedded in a mosaic of Eucalyptus stands. We then tested for differences in the abundance, species richness, species composition, and ecological traits (forest dependence, sensitivity to forest fragmentation, and diet) of the understory bird assemblages inhabiting both kinds of stands. We expected differences in the structure of the bird assemblages because of the different origins and management strategies (contrary to native stands, Eucalyptus stands were selectively logged in the past). Three stands of each habitat (native and Eucalyptus) were sampled with mist nets during 11 months. Eucalyptus stands had a denser understory, whereas native plantations had a more developed vertical structure and a greater density of native trees. The abundance distribution of bird species was more homogeneous in Eucalyptus than in native stands. Eucalyptus had slightly higher species richness (36 species) than native stands (32 species). The composition of species and the occurrence of the diet, forest dependence, and sensitivity to forest fragmentation categories were similar between habitats. Some bird species (e.g. Turdus leucomelas), however, were more abundant in one habitat over the other. Old stands of Eucalyptus and planted native forest can harbor a diverse bird community similar in structure but not exactly equivalent for individual bird species. Planting native diversified forests and keeping set-aside stands of the exotic tree should be viewed as complementary rather than alternative strategies for maintaining bird diversity within plantations.
Keywords: Bird community; Bird conservation; Bird diet; Bird functional groups; Forest management; Forest structure; Restoration ecology; Understory birds